Animals and the law in antiquity - Olyan, Saul M.; Rosenblum, Jordan, 1979- (Brown Judaic studies ;, 2021)
Animal law has become a topic of growing importance internationally, with animal welfare and animal rights often assuming center stage in contemporary debates about the legal status of animals. While nonspecialists routinely decontextualize ancient texts to support or deny rights to animals, experts in fields such as classics, biblical studies, Assyriology, Egyptology, rabbinics, and late antique Christianity have only just begun to engage the topic of animals and the law in their respective areas. This volume consists of studies by scholars from a range of Mediterranean and West Asian fields on animals and the law. Contributors include Rozenn Bailleul-LeSuer, Beth Berkowitz, Andrew McGowan, F. S. Naiden, Saul M. Olyan, Seth Richardson, Jordan D. Rosenblum, Andreas Schüle, Miira Tuominen, and Daniel Ullucci. The volume is essential reading for scholars and students of both the ancient world and contemporary law.--